1991
DOI: 10.1002/yea.320070504
|View full text |Cite
|
Sign up to set email alerts
|

Glucan structure in a fragile mutant of Saccharomyces cerevisiae

Abstract: The phenotype of VY1160 fragile Saccharomyces cerevisiae mutant is characterized by cell lysis upon transfer to hypotonic solutions and increased permeability of cells growing in osmotically stabilized media. Two mutations, srb1 and ts1, have been identified in VY1160 cells and previous studies have shown that the increased permeability is due to the ts1 mutation which causes a shortening of mannan side-chains. Here we report that the srb1 mutation, which is the genetic determinant of cell lysis, is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Other types of screenings directed more specifically towards the detection of ␤-glucan-defective mutants have been undertaken. In some cases, the aim has been to isolate osmotically fragile mutants defective in ␤-glucan synthesis in S. cerevisiae (4,36) and in Schizosaccharomyces pombe (52). In this way, S. pombe mutants affected either directly or indirectly in the particulate or in the detergent-solubilized component of (1,3)␤-D-glucan synthase have been isolated (14,52).…”
mentioning
confidence: 99%
“…Other types of screenings directed more specifically towards the detection of ␤-glucan-defective mutants have been undertaken. In some cases, the aim has been to isolate osmotically fragile mutants defective in ␤-glucan synthesis in S. cerevisiae (4,36) and in Schizosaccharomyces pombe (52). In this way, S. pombe mutants affected either directly or indirectly in the particulate or in the detergent-solubilized component of (1,3)␤-D-glucan synthase have been isolated (14,52).…”
mentioning
confidence: 99%
“…As shown in Table 1, S. cerevisiae 211 cells contained 51% protein and 7% nucleic acids. Its polysaccharide content (23%) was lower compared to other strains, which is due to the decreased contents of manoproteins and alkali-soluble glucan found in previous analytical determinations of cell wall components of the fragile S. cerevisiae mutants [15,16]. Unlike any other strain, however, S. cerevisiae 211 produced biomass with a very high degree of digestability.…”
Section: Composition Of the Yeast Subcellular Fractions And Potentialmentioning
confidence: 53%
“…Work on strains carrying the srb1-1 mutation found a number of cell-wall changes, including alterations in glucan structure and composition (Blagoeva et al, 1991), and mannan content (Maerkisch et al, 1983). Investigations on the mode of action of actinomycin D (Waltschewa et al, 1976) and rifampicin (Venkov et al, 1975) have been facilitated by the hypersensitivity to antibiotics shown by strains carrying the srb1-1 mutation.…”
Section: Psa1-leu2mentioning
confidence: 99%
“…Additional phenotypes include the ability to lyse upon hypotonic shock, antibiotic hypersensitivity and increased permeability of the cell wall and membrane due to defects in their structure and composition (Maerkisch et al, 1983 ;Blagoeva et al, 1991 ;Kopecka et al, 1991). In a previous study (Stateva et al, 1991), a yeast chromosomal gene was isolated that complemented sorbitol dependence in a number of srb strains, including 4STLU.…”
Section: Psa1/vig9 Encoding Gdp-mannose Pyrophosphorylase Is the Bomentioning
confidence: 99%